Budaya Thrifting dalam Membentuk Daya Konsumsi Remaja - Soenaryo, Terry Franka; Bakti, Muhammad Iqbal Putra; Gleetus, Ario; Yanto, Hendy Defri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Thrifting has become a popular culture in contemporary society because it contains branded goods that are the favorite of teenagers. Branded goods available in thrifting are offered at low prices, making many people target them. However, their interest in branded goods is not only to fulfill their body needs, but is more inclined to self-image in social life. With many people wanting to image themselves through branded goods, thrifting has become a popular culture today, especially among teenagers. Without realizing it, they are playing with the signs and symbols in the clothes, so that teenagers' consumption is shaped by the desire for sign value. The purpose of this research is to describe the symbol games that occur in thrifting culture and lead to their desire to get it, so that the original reality is replaced with a fake reality. This research uses a qualitative method, the approach used is phenomenology which is used to understand the symbol games in individuals involved in thrifting culture.